2019
DOI: 10.1021/acs.jpcb.8b09245
|View full text |Cite
|
Sign up to set email alerts
|

Toward Ab Initio Protein Folding: Inherent Secondary Structure Propensity of Short Peptides from the Bioinformatics and Quantum-Chemical Perspective

Abstract: By combining bioinformatics with quantumchemical calculations, we attempt to address quantitatively some of the physical principles underlying protein folding. The former allowed us to identify tripeptide sequences in existing protein three-dimensional structures with a strong preference for either helical or extended structure. The selected representatives of pro-helical and pro-extended sequences were converted into "isolated" tripeptidescapped at N-and C-terminiand these were subjected to an extensive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 69 publications
(94 reference statements)
2
39
4
Order By: Relevance
“…We would like to declare upfront that we do not intend/propose to use the residue folding degree as a substitute for SS defining algorithms. The dynamical aspects of stabilising effects of proteins SS are studied elsewhere [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…We would like to declare upfront that we do not intend/propose to use the residue folding degree as a substitute for SS defining algorithms. The dynamical aspects of stabilising effects of proteins SS are studied elsewhere [ 52 , 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, the backbone-based theory postulates that the universality of the osmolyte effect points to the conclusion that self-organisation takes place mainly in the main chain (Rose et al 2006 ; Dill et al 2008 ). A recent ab initio study confirmed that such a small unit as tripeptides fragments composed of standard amino acids already exhibit a small tendency to adopt a particular secondary structure (helical or extended) (Culka et al 2019 ). Regardless of the chosen theory, it is sure that the conformational preferences of amino acid residues or short peptide fragments have a high impact on the overall secondary structure.…”
Section: Introductionmentioning
confidence: 93%
“…The capability of changing ligand conformation to improve binding affinity in proteins is one of the biomolecular engineering tools crucial for drug discovery and design (Lassila 2010 ; Gagné et al 2012 ; Boehr et al 2018 ; Ding et al 2020 ; Aguesseau-Kondrotas et al 2019 ). Mapping the conformational space of small peptide fragments is also an important prerequisite in decoding the protein folding process and understanding protein structure (Culka et al 2019 ; Culka and Rulíšek 2019 , 2020 ; Ganesan and Paranthaman 2020 ; Chahkandi et al 2014 ). According to the funnel landscape theory, the side chains are primarily responsible for folding diversity.…”
Section: Introductionmentioning
confidence: 99%
“…This choice of training set properties is justified by the potential target applications of small basis set HF based methods, namely fast geometry optimizations and non-covalent interaction strengths in large systems as well as high-throughput 87 screening of conformers in combination with conformer search techniques [88][89][90] . These applications are useful, for instance, when performing exhaustive conformational searches of macrocyclic drugs [91][92][93][94][95][96] and other pharmaceutical candidates 97 , and studying biochemical processes like protein folding [98][99][100] and puckering of nucleotides 101,102 .…”
Section: Training and Validation Data Setsmentioning
confidence: 99%